Enhancing Fifth-Grade Students’ Learning Outcomes Through Interactive Learning Media at SD Negeri 01 Koto Besar - Lillah, Lillah; Dawiri, Dawiri; Rizky, Miftahu (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This Classroom Action Research (CAR) is based on a study aimed at improving the learning outcomes of fifth-grade students through the use of Interactive Learning Media (ILM) at SD Negeri 01 Koto Besar. The objective of this study is to identify the process of implementing interactive learning media in fifth-grade classes at SDN 01 Koto Besar and to determine the improvement in student learning outcomes following the implementation of the media. The Classroom Action Research was conducted in two cycles. The subjects of the study were 20 fifth-grade students at SD Negeri 01 Koto Besar. The data collection technique used in this research focused on students’ learning outcomes. The results showed that the implementation of interactive learning media could enhance student learning outcomes. This is evident from the increasing percentage of students participating in online learning using interactive learning media. In the first cycle, the average percentage of student learning outcomes was 57.5%. In the second cycle, this average increased to 81.5%. Based on the analysis of the research data, it can be concluded that there was a significant improvement in student learning outcomes through the use of interactive learning media in Islamic Education learning for fifth-grade students at SD Negeri 01 Koto Besar in the 2024/2025 academic year.